Pregnancy Tumor in a 31-Year-Old Female with a Facial Port-Wine Stain - Andrew Rockafellow; Whitney Florin; Elizabeth Philipone; David Koslovsky (Case Reports in Dentistry)
Pyogenic granuloma is a type of inflammatory hyperplasia often seen in the oral cavity and occurs in response to stimuli such as local irritants and hormonal factors. Pyogenic granulomas associated with pregnancy are referred to as pregnancy tumors. This report describes the presentation and surgical management of a large pregnancy tumor occurring in a patient with an overlying isolated facial port-wine stain.